The moderating role of e-health literacy and patient-physician communication in the relationship between online diabetes information-seeking behavior and self-care practices among individuals with type 2 diabetes - Maryam Peimani; Anita L. Stewart; Robabeh Ghodssi-Ghassemabadi; Ensieh Nasli-Esfahani; Afshin Ostovar (BMC Primary Care)
Abstract Background This study examined the moderating role of e-health literacy (eHL) and patient-physician communication in the relationship between online diabetes information-seeking behavior (online DISB) and self-care practices. Methods A total of 1143 individuals with type 2 diabetes mellitus completed a cross-sectional survey assessing sociodemographic characteristics, data relating to diabetes clinical history, online DISB, eHL (eHealth Literacy Scale), aspects of patient-physician communication (IPC survey), patient self-care (Self-Care Inventory-Revised), and medication adherence (measure of adherence to prescribed diabetes medications). The data were analyzed using both bivariate (correlation) and multivariate (multiple linear regression) analyses using maximum likelihood estimation procedures in Mplus. Results Our results showed online DISB significantly predicted diabetes self-care (p < 0.001) and medication adherence behaviors (p = 0.005). Lower Hurried Communication (p < 0.001, p = 0.03), higher Elicited Concerns (p = 0.005, p = 0.03), higher Explained Results (p = 0.03, p = 0.008), and higher eHL (p = 0.02, p = 0.02) were significantly associated with better self-care and medication adherence. Explained Results and eHL moderated the relationship between online DISB and both self-care and medication adherence. Conclusions Findings support the role of patient eHL and patient-physician communication in amplifying the positive impact of online DISB on patients’ behavioral outcomes in diabetes.